The surgical management of facial trauma in British soldiers during combat operations in Afghanistan. Issue 1 (January 2017) - Wordsworth, Matthew; Thomas, Rachael; Breeze, John; Evriviades, Demetrius; Baden, James; Hettiaratchy, Shehan
Abstract: Introduction: The recent Afghanistan conflict caused a higher proportion of casualties with facial injuries due to both the increasing effectiveness of combat body armour and the insurgent use of the improvised explosive device (IED). The aim of this study was to describe all injuries to the face sustained by UK service personnel from blast or gunshot wounds during the highest intensity period of combat operations in Afghanistan. Methods: Hospital records and Joint Theatre Trauma Registry data were collected for all UK service personnel killed or wounded by blast and gunshot wounds in Afghanistan between 01 April 2006 and 01 March 2013. Results: 566 casualties were identified, 504 from blast and 52 from gunshot injuries. 75% of blast injury casualties survived and the IED was the most common mechanism of injury with the mid-face the most commonly affected facial region. In blast injuries a facial fracture was a significant marker for increased total injury severity score. A facial gunshot wound was fatal in 53% of cases. The majority of survivors required a single surgical procedure for the facial injury but further reconstruction was required in 156 of the 375 of survivors aero medically evacuated to the UK. Conclusions: The presence and pattern of facial fractures was significantly different in survivors and fatalities, which may reflect the power of the blast that these cohorts were exposed to. The Anatomical Injury Scoring of the Injury Severity Scale was inadequate for determining the extent of soft tissue facial injuries and did not predict morbidity of the injury.